Game Theorical Concept for Denial of Services (DoS) Attacks - Puri Ratna Larasati; Bambang Suharjo; Richardus Eko Indrajit; H.A Danang Rimbawa (Departement of Mathematics Education, 2023)
Information security is a crucial aspect in today's digital era, where increased connectivity and data exchange involves a high risk of denial of services attacks. Increasing cybersecurity and privacy issues require more effective defense mechanisms to counter these threats. This research was conducted through design formulation using game theory for denial of service attacks. First scheme , use Bayes' theorem to determine the probability of a DDoS attack. The probability is equal. The probability of attack and defense is 50-50. Second scheme, one of players is dominan. A game theoretic framework as an approach to find out the possibility of denial of services between pairs of attacking/defending nodes using a Bayesian formulation. Game modeling can propose for developing better mitigation and detection approaches.